التدوير التنظيمي في ظل كل من تراكم الاداء وقوة التطلع واثره في الفساد - سموعى، رفاء فرج (كلية المنصور الجامعة, 2011)
تشكل حالة الفساد في المنظمات الحكومية واحدة من أكبر المشكلات المعاصرة لا على مستوى بلدنا وما أصابه من ويلات بل على مستوى العالم اجمع ولكن ما وصلت إليه منظماتنا (خامس أكثر دولة تعاني من فساد ضمن مائة وثمانين دولة)، يضعنا أمام مسؤولية دراسة هذه الظاهرة من جوانبها كافة، كما أن التدوير التنظيمي هو أحد المرتكزات التنظيمية التي تلجا إليها المنظمات لتحقيق حالة الفاعلية لمواردها البشرية وغيابها عن منظماتنا يضعنا في حقل المظمات البائسة القليلة النجاح والتألق. إن هذا مصير لا يرتضيه أي من القادة المعنيين في منظماتنا ونحن في القرن الواحد والعشرين بكل متطلباته الراقية كلها، ولهذا تبنى الباحث هذين المتغيرين الفساد (الحجم، عمق الاستفحال) والتدوير التنظيمي (قوة التطلع، التراكم الأدائي للعمل). \ يهدف البحث لجملة أهداف منها قياس أثر التدوير التنظيمي في الفساد لكل من الحجم وعمق الاستفحال، توضيح مستوى التدوير والفساد في المنظمة قيد التطبيق، ترتيب الأهمية لمكونات الفساد والتدوير ضمن عينة الأعضاء وموظفي اللجان العاملة في مجلس محافظة بغداد، وبغية التحقق من تلك الأهداف وضع الباحث ستة فرضيات رئيسة وثمانية وعشرون فرضية فرعية، واعتمد الباحث منهجين هما البحث القائم والتحليل البعدي إلى جانب نهج دراسة الحالة.وقد لاقى الباحث صعوبات في جمع وتوزيع استبانة البحث، وتوصل البحث إلى غياب تأثير للتدوير التنظيمي بالفساد بمجموعه مع وجود تأثير الخبرة \ والتغذية العكسية بالفساد بمجموعها للأعضاء وتأثير المكافأة بالفساد للموظفين، واختلاف ترتيب الأهمية للمكونات الفرعية على وفق إجابات الفئتين باستثناء الحاجة إلى الاحترام والرغبة بأداء مهام غير المهام الحالية ووجود إدراك التعاون الثنائي. The organizational recycling is one of the pillars which organizations depend on to achieve activation of their human resources .However lacking this in our organizations means that these organizations are in desperate conditions and that thy can not attain success and prosperity . The level of corruption in our organizations (fifth out of one hundred eighty states suffering from corruption) also presents us with the responsibility of studying every aspect of this overwhelming phenomenon. This cannot be satisfy the leading officials in our organizations considering the fact that we live in the twenty first century. \ Thus, the researcher has adopted the two variables of corruption (size and scope) and organizational recycling (power of ambition and the accumulative performance of work). The paper aims at a number of goals, one of which is measuring the effect of organizational recycling effect on corruption in terms of size and scope. Others are clarifying the level of corruption and recycling in the organization under study,arranging the importance of corruption and the recycling within a sample of member and officials in the committees of Baghdad city Council . To verify these goals, the researcher has introduced six major hypotheses and sixty minor ones, by following two main approaches standing research and dimensional analysis in addition to case study approach. The researcher has met with difficulties concerning collecting and distributing the paper’s Questionnaire and has concluded that organizational recycling has no effect on corruption. With the existence of the experience and feedback factors which has effects on corruption among members, the effect of reward on corruption among officials , the various importance arrangement for minor components according to the answers of the two section except the need for respect and the readiness to do more task than the current ones, and the awareness of the other party cooperation.
818882
Keywords: فاعلية الموارد البشرية -- المنظمات الحكومية -- الفساد -- التدوير التنظيمي -- التدوير الوظيفي -- الاداء الوظيفي